Optimisation of soaking conditions to improve the quality of frozen fillets of bocourti's catfish (Pangasius bocourti Sauvage) using response surface methodology (RSM) - Chaluntorn Vichasilp (2018)
© Universiti Putra Malaysia Press. Bocourti's catfish (Pangasius bocourti Sauvage) is one of Asia's economic freshwater fish. The fish has high demand in Asian markets particularly as a frozen product due to its tasty meat and a size that makes it suitable for cooking as fish steak. However, there are few studies about its production and quality. For frozen products, soaking in appropriate chemicals and conditions is the key procedure that food producers use to improve the quality of the frozen fillet. Therefore, this research aims to establish the optimum conditions for soaking. Several phosphate compounds, sodium acid pyrophosphate (SAPP), tetra sodium pyrophosphate (TSPP), sodium tripolyphosphate (STPP) and sodium hexametaphosphate (SHMP), were investigated. It was found that the best phosphate compound was STPP that provided high L ∗ , a ∗ , gained weight, cooking yield and sensory acceptability with less drip loss and cooking loss. Consequently, the optimisation of the soaking condition was conducted. The three main factors, STPP (0.13-4.38% w/v), soaking time (3-37 min) and salt concentration (0.30-3.70% w/v), were optimised by response surface methodology (RSM). The results showed that the optimised condition was STPP of 2.56%, soaking time of 37 min and salt concentration of 3.70%. At this condition, the obtained frozen fillets showed a good result with gained weight of 11.45%, cooking yield of 73.11%, a ∗ of 10.97 and °h of 9.94, respectively.